Colonoscopy to diagnose chronic ulcerative colitis in an 11-years-old Maltese - Fitria Senja Murtiningrum; Deni Noviana (ARSHI Veterinary Letters, 2020)
An 11-year-old castrated male Maltese was examined for increased frequency of defecation, mucus in feces, and chronic diarrhea with hematochezia. The dog was referred to Veterinary Teaching Hospital, Faculty of Veterinary Medicine, IPB University for further evaluation. Ultrasonography and colonoscopy were performed to further diagnose. Abdominal ultrasonography was taken using a linear probe with frequency 6-11 MHz. Colonoscopy was performed using colonoscope with tube length 700 mm and diameters 10 mm under anesthesia. Abdominal ultrasonography showed that the dog had a mucocele gall bladder, cholecystitis, hepatitis, slight-mild splenitis, nephrolithiasis, urolithiasis and thickened of the duodenal wall due to inflammatory bowel diseases. Colonoscopy showed ulceration and hemorrhage along the surface of the colon, whereas hyperemia only seen on the ascending colon. Based on endoscopic examination, the dog was diagnosed with severe and chronic ulcerative colitis. The authors recommended that the colonic biopsy should be undertaken in the dog presented with chronic ulcerative colitis.